Critical macro-finance, Post Keynesian monetary theory and emerging economies - Bruno Bonizzi; Annina Kaltenbrunner (Finance and Society, 2020)
In our contribution to this forum, we suggest that critical macro-finance (CMF) scholars and Post Keynesian monetary theorists would profit from a more explicit engagement with each other. Post Keynesian scholars would benefit from the detailed empirical insights that CMF provides, particularly through its analysis of non-bank financial institutions and the conceptual focus on liquidity and liabilities. Meanwhile, the CMF literature would benefit from more explicit grounding in earlier Post Keynesian concepts. In particular, the theory of liquidity preference, the concept of the liquidity premium, and the theory of endogenous money highlight macroeconomic issues missing from CMF scholarship.
Keywords: 300